To Ruin the Repairs: Milton, Allegory, Transitional Justice. (October 2019) - Warren, Christopher
International legal theorists posit historical moments when conceptions of justice are "constituted by, and constitutive of, the transition" (Teitel). This article uses the framework of transitional justice to understand the cultural work of political allegory in the spring of 1660 on the eve of the English Restoration. Insights from transitional justice (1.) help explain how Anglican royalists convinced wary Presbyterians to assent to a restoration of the monarchy; (2.) permit a new reading of Milton's allegory of Sin and Death in Paradise Lost ; and (3.) facilitate a more critical history of the framework of transitional justice itself.